Akibat Hukum Notaris Menggunakan Website Pribadi Dalam Memberikan Pelayanan Jasa Kepada Masyarakat - Kinasih, Nadia Pitra; Himma, Azizahtul (PT Matra Cendikia Abadi, 2024)
The use of Notary websites is now widely used by Notary Public groups in various regions. As we know, it has not been specifically regulated in the Law on the Position of Notaries or the Code of Ethics regarding websites as intermediaries between clients and Notaries. This legal vacuum has caused Notaries to start opening services via personal websites. However, there are still pros and cons related to the use of electronic media in Notary services through websites that are currently being carried out, whether the use of websites or other electronic media is allowed or not in Notary Services and their legal consequences. The type of research used is the normative legal research method. The approach used is the statutory and conceptual approach which is analyzed using qualitative methods. The results of this study indicate that first, the use of electronic media in Notary services through websites is permitted as long as it only provides legal consultation or counseling in the civil field. While the use of electronic media in Notary services through websites that is prohibited is on the Notary's personal website containing elements of self-promotion such as including the name and title of office, exposing Notary activities on the website such as photos with clients. Second, the legal consequences for Notaries regarding the use of electronic media in Notary services are the imposition of sanctions on Notaries if they are proven to have carried out self-publication which can bring down the honor and dignity of the Notary's position in the form of a written warning and can even be subject to punitive sanctions, namely in the form of temporary dismissal, even honorable dismissal. or disrespect. Keywords : Notary; Website; Services.